A fully automatic group selection for form-finding process of truncated tetrahedral tensegrity structures via a double-loop genetic algorithm. (1st December 2016) - Lee, Seunghye; Gan, Buntara Sthenly; Lee, Jaehong
Abstract: Numerous studies have developed novel form-finding methods of tensegrity structures using various techniques. Previous works have been limited by the lack of a fully automatic grouping technique in the form-finding process. In this study, an advanced form-finding method of tensegrity structures using a fully automatic labeling that can specify the member types. Constraint optimization problems were then used in the form-finding processes to minimize fitness functions by using a double-loop genetic algorithm. A well-known truncated tetrahedral tensegrity is presented to demonstrate the accuracy and efficiency of the proposed method. In conclusion, a very good performance of presented method has been shown in the results. Highlights: An advanced method for form-finding of tensegrity structures is presented. A fully automatic group selection can be obtained using a penalty strategy with discrete strut condition. A double-loop GA is used to effectively guide the searching direction towards promising solutions. The constraint minimization problems by using the equilibrium equations are used. A very good performance of presented method has been shown in the results.